PARADIGMA PENDIDIKAN AGAMA ISLAM DI INDONESIA - Syoviana, elvi (Jurnal Sakinah, 2019)
Islamic education as "the set-up process of the young generation to fill the role of moving knowledge and Islamic values are aligned with the human function for charity in the world and picking the result in the afterlife. In Arabic there are three terms used to denote the meaning of education al-tarbiyah al-ta'lim and al-ta'dib. Awareness and strong desire of the Government and the people of Indonesia to improve the education system is the most important thing is to realize that Indonesia's intellectual education can change all the systems that are in Indonesia. Now the nation of Indonesia living in the era of globalization and the Reformation era it was much different from the circumstances in the past. All changes that occur from the time this now affects all systems of education in Indonesia. All components of the system of education which has been owned by different components of the education in the past. Accordingly, Thus, all educational institutions from the most basic level to the College must follow all the process change from time to time to maintain the existence in the world of education and contribute to the preparation of the future a better nation. With reference to the various references uptodate education, as well as with a fixed based on the spirit of Islamic teachings as contained in the Qur'an and as-Sunnah.